Myelin Oligodendrocyte Glycoprotein (MOG) Antibody Diseases in Children in Central South China: Clinical Features, Treatments, Influencing Factors, and Outcomes - Mao, Leilei; Yang, Lifen; Kessi, Miriam; He, Fang; Zhang, Ciliu; Wu, Liwen; Yin, Fei; Peng, Jing (Frontiers in Neurology, 2019)
Background and purpose: The clinical and radiological features of myelin oligodendrocyte glycoprotein antibody (MOG-Ab) diseases vary among the patients and studies. In addition, the clinical significance of MOG-Ab for the diagnosis, treatment, and prognosis is not yet established. Therefore, we aimed to evaluate the clinical, radiological, treatments and outcome features of MOG-Ab diseases in Central Southern part of China. Methods: A retrospective study of children with MOG-Ab disease was carried out from January 2015 to October 2018. Demographics, clinical features, treatments, and outcomes were reviewed. Some of the clinical information was compared including the annualized relapse rates (ARRs) before and after treatment with disease-modifying drugs (DMDs). Results: Twenty-five patients with MOG-Ab disease were recruited. The onset age ranged from 3 to 12.4 years old. 13 were females and 12 were males. The median follow-up period was 15 months (range 7–63). Most of the cases that aged ≤9 years presented with fever (47.4%), encephalopathy (47.4%), and lesions on white matter and/or deep gray matter (52.6%). While most of those aged above 9 years presented with optic neuritis (ON) (66.7%), and lesions on spinal cord and/or optic nerve (50%). Until the last follow-up, 10 (40%) cases had multiphasic courses while 15 (60%) had a monophasic course, and the mean follow-up time was statistically significant (10.67 vs. 31 months, p = 0.0001). DMDs such as rituximab (RTX) or/and azathioprine (AZP) or mycophenolate mofetil (MMF) were used at least once in 56% of the cases. The ARR before and after treatment was 2.4 and 0 respectively (p < 0.05). The median Expanded Disability Status Scale scores of our study were 0 (range 0–2). 96% (24/25) of the cases had a full recovery. Conclusions: MOG-Ab disease among Chinese children share the same clinical characteristics with Caucasians. However, the Chinese children seem to have a better prognosis than Caucasians. There is an age-dependent phenotypes, as brain involvement is more frequently seen in children younger or equal to 9 years while ON and neuromyelitis optica spectrum disorders are commonly seen in children older than 9 years. DMDs, such as AZA, MMF or RTX, can reduce the ARR.